2022
DOI: 10.1111/nph.18174
|View full text |Cite
|
Sign up to set email alerts
|

PICKLE associates with histone deacetylase 9 to mediate vegetative phase change in Arabidopsis

Abstract: The juvenile-to-adult vegetative phase change in flowering plants is mediated by a decrease in miR156 levels. Downregulation of MIR156A/MIR156C, the two major sources of miR156, is accompanied by a decrease in acetylation of histone 3 lysine 27 (H3K27ac) and an increase in trimethylation of H3K27 (H3K27me3) at MIR156A/MIR156C in Arabidopsis.Here, we show that histone deacetylase 9 (HDA9) is recruited to MIR156A/MIR156C during the juvenile phase and associates with the CHD3 chromatin remodeler PICKLE (PKL) to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 64 publications
(164 reference statements)
1
5
0
Order By: Relevance
“…In this study, we developed a deficient mutant of Arabidopsis HDA9 ( hda9 ), with a single amino acid substitution, HDA9 Q337H . Similar to other HDA9 mutants, hda9 exhibits an early flowering phenotype in short-day conditions, but a delayed phase transition (Fig.3B-G & S25 -26) 30, 45 . This suggests that the 337th amino acid, glutamine, is crucial for the function of HDA9 in both aging and flowering signal pathways.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In this study, we developed a deficient mutant of Arabidopsis HDA9 ( hda9 ), with a single amino acid substitution, HDA9 Q337H . Similar to other HDA9 mutants, hda9 exhibits an early flowering phenotype in short-day conditions, but a delayed phase transition (Fig.3B-G & S25 -26) 30, 45 . This suggests that the 337th amino acid, glutamine, is crucial for the function of HDA9 in both aging and flowering signal pathways.…”
Section: Discussionsupporting
confidence: 63%
“…However, our work demonstrates that TAL1 can interact with HDA9 within the 5’ up-stream of the MIR156A gene body to regulate miR156A expression and chromatin remodeling (Fig. 3I & S16) 30 . Histone deacetylase family proteins exhibit high functional diversity and can function as both chromatin deacetylases and acetylases for the same member 46, 47 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In Arabidopsis , trimethylation of histone H3 Lys 27 (H3K27me3) is deposited by Polycomb Repressive Complex 2 (PRC2; Hinsch et al ., 2021). PICKLE (PKL) is an ATP‐dependent Chromodomain Helicase DNA‐binding domain type 3 (CHD3) chromatin remodeler that is required for H3K27me3 deposition at some genomic locations and regulates multiple plant developmental and physiological processes (Tong et al ., 1998; Ogas et al ., 1999; Fukaki et al ., 2006; Perruc et al ., 2007; Aichinger et al ., 2009, 2011; Furuta et al ., 2011; Jing et al ., 2013, 2019a,b; Zhang et al ., 2014; Xu et al ., 2016; Zha et al ., 2017, 2020; Yang et al ., 2019; Hinsch et al ., 2021; Hu et al ., 2022; Liang et al ., 2022). A recent study revealed that PKL could interact with the transcription factors VIVIPAROUS1/ABI3‐LIKE1/2 (VAL1/2) to repress the expression of ABA INSENSITIVE 3 ( ABI3 ) and AGAMOUS‐LIKE 15 ( AGL15 ) in regulating the seed‐to‐seedling transition (Liang et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, 18 HDA genes have been categorized into three different families: (i) reduced potassium dependence 3/histone deacetylase (RPD3/HDA1, 12 members), (ii) silent information regulator 2 (SIR2, 2 members), and (iii) plant‐specific histone deacetylase 2 (HD2, 4 members) (Hollender & Liu, 2008; Jang et al., 2003). HDA9 as a member of RPD3/HDA1 family has been extensively studied for its role as a gene suppressor involved in Arabidopsis growth and development including seed dormancy and germination (van Zanten et al., 2014), leaf development (Suzuki et al., 2018), thermomorphogenesis (Tasset et al., 2018), abiotic stress (Baek et al., 2020; Zheng et al., 2016), autophagy (Yang et al., 2020), hypocotyl elongation under short day photoperiod (Lee et al., 2022), floral transition (Chu et al., 2022; Hu et al., 2022; Kim et al., 2013, 2016; Mayer et al., 2019; Park et al., 2019; Zeng et al., 2020) and leaf senescence (Chen et al., 2016). Besides, several studies have implied that HDA9 may have an atypical function of regulating gene activation (Chen et al., 2016; Shen et al., 2019; van der Woude et al., 2019).…”
Section: Introductionmentioning
confidence: 99%